2002
DOI: 10.1073/pnas.052556499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of the insect adipokinetic hormone receptors

Abstract: The insect adipokinetic hormones (AKHs) are a large family of peptide hormones that are involved in the mobilization of sugar and lipids from the insect fat body during energy-requiring activities such as flight and locomotion, but that also contribute to hemolymph sugar homeostasis. Here, we have identified the first insect AKH receptors, namely those from the fruitfly Drosophila melanogaster and the silkworm Bombyx mori. These results represent a breakthrough for insect molecular endocrinology, because it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
189
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(193 citation statements)
references
References 36 publications
3
189
1
Order By: Relevance
“…Two days before the assay, the cells were transiently transfected with DNA, coding for apoaequorin; coelenterazine was added to the culture medium 3 hours before the assay. Addition of receptor ligands and activation of the receptors in these pretreated cells would lead to an inositol 1,4,5-trisphosphate (IP 3 )͞Ca 2ϩ -mediated bioluminescence response that could easily be measured and quantified (22,23,(26)(27)(28)(29)(30)(31)(32). We tested a peptide library (consisting of 24 Drosophila or other invertebrate neuropeptides), and seven monoamines on these cells and found that the two receptors were activated by low concentrations of Drosophila myosuppressin (Drome-MS) (5, 11).…”
Section: Resultsmentioning
confidence: 99%
“…Two days before the assay, the cells were transiently transfected with DNA, coding for apoaequorin; coelenterazine was added to the culture medium 3 hours before the assay. Addition of receptor ligands and activation of the receptors in these pretreated cells would lead to an inositol 1,4,5-trisphosphate (IP 3 )͞Ca 2ϩ -mediated bioluminescence response that could easily be measured and quantified (22,23,(26)(27)(28)(29)(30)(31)(32). We tested a peptide library (consisting of 24 Drosophila or other invertebrate neuropeptides), and seven monoamines on these cells and found that the two receptors were activated by low concentrations of Drosophila myosuppressin (Drome-MS) (5, 11).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is intriguing that the cognate ligand for these receptors is not GnRH and that GnRH evolved later as a ligand for the receptor. In Drosophila, the cognate ligand is a nonapeptide called adipokinetic hormone [134].…”
Section: Gnrh Receptor Structure and Functionmentioning
confidence: 99%
“…Even though no role of APRP was described so far (Hatle and Spring 1999), its evolutionary conservation, common ancestry with mammalian growth hormone-releasing factors (Clynen et al 2004), and release upon stimulation with melatonin (Huybrechts et al 2005) all argue in favor of an endocrine function of this peptide. Thus, unequivocal study of AKH and APRP functions requires creation of specific mutants, which we describe in this study.Biochemical studies identified a single Drosophila AKHR receptor (Park et al 2002;Staubli et al 2002), which has been functionally analyzed in vivo (Grönke et al 2007;Bharucha et al 2008). However, these studies do not exclude AKH signal transmission via other receptor pathways.…”
mentioning
confidence: 99%
“…Biochemical studies identified a single Drosophila AKHR receptor (Park et al 2002;Staubli et al 2002), which has been functionally analyzed in vivo (Grönke et al 2007;Bharucha et al 2008). However, these studies do not exclude AKH signal transmission via other receptor pathways.…”
mentioning
confidence: 99%